Between Silence and Speaking: the Representation of National Identity in Oksana Zabuzhko’s Poetry - Borysiuk, Iryna (Tematy i Konteksty, 2017)
The article is focused on the problems of national identity, self-representation, and memory re-articulation in Oksana Zabuzhko’s poetry. Language, speaking, and word as well as silence are conceptualized as key concepts in verse by the 1980s generation of Ukrainian poets to whom Oksana Zabuzhko belongs. Speaking and silence in 1980s poetry can be treated not only as concepts or metaphors but also as a literary strategy or even as the form of resistance in the late Soviet era. The article is structured as the gradation of motives from speaking to silence in Zabuzhko’s poetry. The analyses includes the following subthemes: non-verbal language represented by sounds, gestures, and poses, verbal language as existing between sacrum and profanum, speechlessness, and silence.